-6(6r+3)+5(r+5)=69

Simple and best practice solution for -6(6r+3)+5(r+5)=69 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(6r+3)+5(r+5)=69 equation:


Simplifying
-6(6r + 3) + 5(r + 5) = 69

Reorder the terms:
-6(3 + 6r) + 5(r + 5) = 69
(3 * -6 + 6r * -6) + 5(r + 5) = 69
(-18 + -36r) + 5(r + 5) = 69

Reorder the terms:
-18 + -36r + 5(5 + r) = 69
-18 + -36r + (5 * 5 + r * 5) = 69
-18 + -36r + (25 + 5r) = 69

Reorder the terms:
-18 + 25 + -36r + 5r = 69

Combine like terms: -18 + 25 = 7
7 + -36r + 5r = 69

Combine like terms: -36r + 5r = -31r
7 + -31r = 69

Solving
7 + -31r = 69

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '-7' to each side of the equation.
7 + -7 + -31r = 69 + -7

Combine like terms: 7 + -7 = 0
0 + -31r = 69 + -7
-31r = 69 + -7

Combine like terms: 69 + -7 = 62
-31r = 62

Divide each side by '-31'.
r = -2

Simplifying
r = -2

See similar equations:

| 5x+18=6x+14 | | x+132=125 | | 6(2+6k)-8=-176 | | -(b-5)=b-3 | | -3(-2+x)=-10 | | -11+a=-2(7a-2) | | 19r=-57 | | x^2+(1-i)x-i=0 | | -4v+2(-1-6v)=-130 | | -2(2y-6)-y=-2(y-3) | | 2a-4=3(a-4) | | x^2+(1-i)x-1=0 | | 2(2y-1)=-19 | | -32+8v=6(v-7) | | 2b^2+3b-2= | | -42=3(6+8b)+6(-3b-7) | | 9x-2=133 | | 60=-5(6n-6) | | 38-n=5+4(-2n+3) | | -26+6p=-8(1-3p) | | 2(r+4)=-35 | | 580=-20b | | 9y+12=84 | | 21x-3=40x | | 2(3-x)=60 | | -5.5=-3.4 | | 7(x-2)=5(x-4) | | -7(7n+7)=39-5n | | 3+r=19 | | 10b^2-15b-8b+12b=0 | | 12x^4+10x^3-12x^2=0 | | -3n-2(-8n-3)=-14+3n |

Equations solver categories